Interactive Learning Media On Dynamic Electrical Materials For Concept-Based High School Students - Siti Hamidah; Suci Prihatiningtyas; Novia Ayu Sekar Pertiwi; Ino Angga Putra (SCHOOLAR: Social and Literature Study in Education, 2026)
The purpose of this study is to develop an interactive learning media based on Canva using the topic of dynamic electricity to increase students' learning interest. The research and development process was carried out using the Borg and Gall development model, which was simplified into several key stages: identifying potential and problems, data collection, product design, design validation, design revision, product testing, product revision, and implementation trial. The validation results of the Canva-based interactive learning media showed that the media received a score of 81.0% from material experts and 78.3% from media experts. Therefore, the interactive learning media are considered feasible and sufficiently effective to be used in physics learning, particularly on the topic of dynamic electricity.